Arterial hypertension in schizophrenia - A. Yu. Tretyakov (Российский кардиологический журнал)
Arterial hypertension (АН) features in schizophrenia were studied by clinical and pathoanatomical methods. In schizophrenic patients, AH was diagnosed later than in internal disease patients; early stages of AH were characterized by moderate progression, regardless of psychotropic therapy regimen. In psychoses, Stage II-III AH was prevalent, being associated with kidney disease and atherosclerosis. Severe schizophrenia and personality defects were linked to moderate severity of initial somatic pathology.